Kecakapan Personal dan Sosial Kelas XI dalam Pembelajaran Sosiologi di SMA Negeri Kalirejo - Yuli Astuti; Sudjarwo Sudjarwo; Risma M Sinaga (Faculty of Teacher Training and Education, University of Lampung, 2019)
The purpose of this study was to analyze personal and social skills. The research method used qualitative research and data collection techniques with observation, interviews, and documentation. The analysis of the research was descriptive. The results showed that students' personal skills in Sociology learning which consisted of indicators of self-awareness and rational skills were still low. The low indicators of self-awareness skills consisting of a) managing time, b) work great, and c) responsible because it was obtained from the results of cheating. Likewise with the indicator of rational skills, namely a) explore and find information, b) processing information, and c) problem solving was also low because students were not focused. While students' social skills varied, the indicators of verbal communication were low because they lack understanding of the material, while non-verbal scores were high because students enjoyed learning. Tujuan penelitian ini adalah untuk menganalisis kecakapan personal dan sosial. Metode penelitian menggunakan penelitian kualitatif dan teknik pengumpulan data dengan observasi, wawancara, dokumentasi. Analisis penelitiannya adalah deskriptif. Hasil penelitian menunjukkan bahwa kecakapan personal siswa pada pembelajaran sosiologi yang terdiri dari indikator kecakapan kesadaran diri dan rasional masih rendah. Rendahnya indikator kecakapan kesadaran diri yang terdiri dari a) mengelola waktu, b) bekerja hebat, c) bertanggungjawab karena diperoleh dari hasil menyontek. Demikian juga pada indikator kecakapan rasional yaitu a) menggali dan menemukan informasi, b) mengolah informasi c) memecahkan masalah juga rendah karena siswa tidak fokus. Sedangkan kecakapan sosial siswa bervariasi yaitu indikator komunikasi verbal rendah karena kurang memahami materi, sementara pada non verbal bernilai tinggi karena siswa senang dalam belajar. Kata Kunci: kecakapan personal, kecakapan sosial, pembelajaran sosiologi.